2013
DOI: 10.1371/journal.pone.0055363
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Attenuates Renal Dysfunction with Preservation of Myocardial Function in Chronic Kidney Disease

Abstract: Previous studies have suggested that exercise improves renal and cardiac functions in patients with chronic kidney disease. The aim of this study was to evaluate the effects of long-term aerobic swimming exercise with overload on renal and cardiac function in rats with 5/6 nefrectomy (5/6Nx). Eight Wistar rats were placed into 4 groups: Control (C), Control+Exercise (E), Sedentary 5/6Nx (NxS) and 5/6Nx+Exercise (NxE). The rats were subjected to swimming exercise sessions with overload for 30 min five days per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…31 Swimming exercise reduced the progression of renal disease in 5/6 nephrectomized rats. 32 Previous exercise training also protects against the progression of diabetic nephropathy produced by streptozotocin-induced diabetes in rats. 33 Most of these studies were intended to mimic the aerobic endurance type of exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…31 Swimming exercise reduced the progression of renal disease in 5/6 nephrectomized rats. 32 Previous exercise training also protects against the progression of diabetic nephropathy produced by streptozotocin-induced diabetes in rats. 33 Most of these studies were intended to mimic the aerobic endurance type of exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…19 The protective role of exercise training on renal damage has been reported in pervious works. 16,20,21 We also considered the effects of SW exercise training alone or supplemented with garlic on renal and hepatic cells apoptotic biomarkers. Interestingly, our data demonstrated that SW exercise, particularly combined with garlic supplementation, enhances the renal and hepatic Bcl-2 levels and reduces the mean value of BAX.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The protective role of exercise training on renal damage has been reported in pervious works. 16 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Moderate and regular exercise has attenuated aging-associated mitochondrial dysfunction (40), improved cognitive performance (41) and memory (42) and positively affected emotional aspects of behavior, resulting in better responses to acute or chronic stressor exposures (43).It was shown that exercise training in rats improved cardiac function following myocardial infarction (44), attenuated endotoxemia-induced lung damage (45) and reduced the progression of renal disease (46). In accordance with these, swimming exercise ameliorated RVH-induced oxidative damage of the kidneys via the inhibition of neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%